Ho Chi Minh - Neville, Peter 1944- (Routledge historical biographies, 2019)
"Ho Chi Minh explores the life of this globally important twentieth century figure and offers new insights into his lengthy career. As well as extensive coverage of the 1954 Geneva Conference, the rivalry between Ho and First Secretary Le Duan and the 1968 Tet Offensive, Ho Chi Minh is also the first English language biography of Ho to pay close attention to his attitude to women and their role within the Communist Party. It is the perfect introduction for students of Vietnamese history and twentieth century history more broadly."--Provided by publisher